EFFECT OF DIFFERENT CONCENTRATION CINNAMON EXTRACTS (CINNAMOMUM BURMANNII) IN GROWTH LACTOBACILLUS ACIDOPHILUS (IN VITRO) - Sherlin Mentary Farizha; Desy Armalina; Diah Ajeng Purbaningrum (Jurnal Kedokteran Diponegoro, 2021)
Background: One of the dental and oral health problem that really need attention is caries. Lactobacillus acidophilus is one of the bacteria that play a role in the process of further caries in dentin. We can control it by using materials like antibacterial. Cinnamon barks (Cinnamomum burmannii) is a plant from Indonesia that contains antibacterial compounds such as sinamaldehid, flavonoid, tannins, alkaloids, and saponins